War and revolution in Russia, 1914-22 : the collapse of Tsarism and the establishment of Soviet power - Read, Christopher 1946- (European history in perspective, 2013)
This introduction synthesises the wealth of new material available on the Russian Revolution into a clear overview which is ideal for beginners. Leading expert Christopher Read treats the period 1914-1922 as a whole in order to contextualise and better understand the events of 1917 and their impact